The Impact of Mortar Properties on the Compressive Strength of a Masonry Prism - Raisul Shuvo; Sharmin Chowdhury; Rukshana Ripa; Sadia Sabrin; Foysal Shohag (Journal of Rehabilitation in Civil Engineering)
\Masonry buildings remain popular worldwide due to their readily available materials, high compressive strength, ease of construction, and affordability. Therefore, understanding the impact of mortar on the compressive strength of masonry is essential. This study aimed to determine the compressive strength and failure patterns of masonry, focusing particularly on mortar. An experimental program was conducted, involving a total of 54 specimens: 27 cubes, 27 cylinders, and 9 masonry prisms. The cement-to-sand ratio (c/s) varied at ratios of 1:3, 1:4, and 1:5, while the water-to-cement ratio (w/c) remained fixed at 0.45. Each prism consisted of 5 bricks separated by a 10 mm mortar layer. Compressive strength data for cubes and cylinders were collected at 3, 7, and 28 days, while data for prisms were collected only at 28 days. The best results have been obtained at a c/s ratio of 1:3, with compressive strengths of 3555.5 psi for cubes, 3282.98 psi for cylinders, and a compressive force value of 129.33 kN for prisms at 28 days. The compressive strength of cubes and cylinders increases by approximately 68.19% and 64.61%, respectively, and the compressive force of masonry prisms increases by approximately 76.48% at 28 days when the cement-to-sand ratio is changed from 1:5 to 1:3. Stresses, graphs, and failure patterns have been analyzed and compared with the Bangladesh National Building Code (BNBC) 2020 and available literature, revealing a strong correlation.